SEKOLAH PEREMPUAN DESA KARAK APUNG - Habibie, Zulqoidi R; Sari, Ratna (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
The dominance of the agricultural world in Karak Apung Village makes the women in the village have farming skills that are no less great than men, as a result in general only those skills can be highlighted for the women of Karak Apung villagers. Through this girls' school, she hopes to solve the village problem which is divided into three things, (1) the Skills Program; (2) Equality Program; and (3) Digital Reading Room Program. The method of treatment will be taken for one semester or 12 face-to-face meetings. The results of the girls' school, namely the women of Karak Apung Village, have been equipped with new competencies, namely Bridal Makeup, Tata Boga, Gymnastics Instructors, and the Village has a digital reading room corner equipped with wifi. This skill is evidenced by the existence of a legal competency certificate owned by the Woman of Karak Apung Village